School-based mental health promotion: A global policy review - Margaretha, Margaretha; Azzopardi, Peter Sebastian; Fisher, Jane; Sawyer, Susan Margaret (Frontiers in Psychiatry, 2023)
Objectives Schools are increasingly recognized as important settings for mental health promotion, but it is unclear what actions schools should prioritize to promote student mental health and wellbeing. We undertook a policy review of global school-based mental health promotion policy documents from United Nations (UN) agencies to understand the frameworks they use and the actions they recommend for schools. Methods We searched for guidelines and manuals from UN agencies through the World Health Organization (WHO) library, the National Library of Australia and Google Scholar, from 2000 to 2021, using various combinations of search terms (e.g., mental health, wellbeing, psychosocial, health, school, framework, manual, and guidelines). Textual data synthesis was undertaken. Results Sixteen documents met inclusion criteria. UN policy documents commonly recommended a comprehensive school-health framework aimed at integrating actions to prevent, promote, and support mental health problems within the school community. The primary role of schools was framed around building enabling contexts for mental health and wellbeing. Terminology was relatively inconsistent across different guidelines and manuals, particularly around how comprehensive school health was conceptualized, which included aspects of scope, focus, and approach. Conclusion United Nations policy documents are oriented toward comprehensive school-health frameworks for student mental health and wellbeing that include mental health within wider health-promoting approaches. There are expectations that schools have the capabilities to deliver actions to prevent, promote and support mental health problems. Implication Effective implementation of school-based mental health promotion requires investments that facilitate specific actions from governments, schools, families, and communities.